(untitled) (Fiep Bulletin - online, 2014)
Muscular flexibility can be defined as the difference between the relaxed and extended position of the muscle. With soccer evolution, injuries are likely to appear due to the fact that every player is trying to overcome their own limits. In this context, flexibility is very important for injuries prevention and performance improvement. The main goal of this study was to compare the posterior inferior muscle’s flexibility in professional and non-professional soccer player groups, relating it to the lumbar spine and inferior members pain complaints. The data were collected by a questionnaire-interview approaching pain, injuries occurrence and kinds of training, as well as body images analysis by Biofotogrametria®. Points were marked on the players’ pelvis and right inferior members according to Santos (2001), requesting them to flex the truncus until the pain limit. To register images, a PENTAX digital camera was used. The data analysis was realized by the simple and decussate frequency distribution. It was verified that the coxofemoral articulation was shown as 44,42º for professional players and 39,89º for non-professional players, being both under the ideal flexibility (90º). Only 3 players related lumbar spine pain or inferior members’ injuries episode which could be related to the shorten of the posterior inferior chain, not finding in this study the relation between these. Conclusion: Besides there’s no relation between pain and flexibility, it is observed the necessity of improving warm up exercises in non-professional as well as in professional teams, because literature brings the importance of extensibility for injuries prevention and athletes’ performance improvement.